Older patients with pulmonary embolism: a state-of-the-art review - Liliana Mazza; Mariagiovanna Cozza; Francesca Flavia Rossi; Roberto Caragnulo; Giulia Mussatti; Annalisa Paglia; Mattia Brunori; Vincenzo Gianturco; Andrea Rossi; Simone Dini (Geriatric Care)
Pulmonary embolism (PE) represents one of the main causes of acute respiratory failure in geriatric patients. In the older population, critical issues in PE management are multiple: reduced specificity of clinical signs and symptoms (with symptoms common to other pathologies, such as chest pain, dyspnea, and tachypnea), frequent late diagnosis (delay in diagnosis or misdiagnosis), the difficulty in the diagnostic algorithm, the need for a rapid prognostic assessment, and consequent timely treatment. Optimal PE management is patient-centered, includes all treatment options available, and aims at optimizing clinical outcomes in the short, medium, and long term with a multidisciplinary approach.